The effect of cation chemistry on physicochemical behaviour of superconcentrated NaFSI based ionic liquid electrolytes and the implications for Na battery performance. (1st April 2018) - Hilder, Matthias; Howlett, Patrick C.; Saurel, Damien; Gonzalo, Elena; Basile, Andrew; Armand, Michel; Rojo, Teofilo; Kar, Mega; MacFarlane, Douglas R.; Forsyth, Maria
Abstract: There is growing interest in ionic liquid based electrolytes for Na metal and Na-ion batteries. Here we compare three quite distinct bis(fluorosulfonyl)imide (FSI) anion based ionic liquids with small alkyl phosphonium (trimethyl iso butyl phosphonium, methyl tri- iso butyl: P111i4, P1i4i4i4 ) or alkoxy ammonium counter cations ( N -ethyl-2-(2-methoxyethoxy)- N, N -bis(2-(2-methoxyethoxy)ethyl)ethan-1-ammonium bis(fluorosulfonyl)imide: N2(2O2O1)3 ) mixed at near 1:1 mol ratio with NaFSI. The conductivities of these electrolytes range from 4.4 mScm −1 for the smallest P111i4 FSI:NaFSI system to 0.3 mScm −1 for the N2(2O2O1)3 FSI:NaFSI mixture at 50 °C. This difference in conductivity is interestingly not reflected in the cyclic voltammetry for Na/Na + where the maximum peak current density of 10 mAcm −2 is surprisingly high for the poorly conductive N2(20201)3 FSI:NaFSI solution (e.g. 17 mAcm −2 for P111i4 FSI:NaFSI). The overpotentials observed for Na symmetric cell cycling show very little differences after initial stabilising/conditioning for the three electrolytes being 50 mV for P111i4 FSI:NaFSI and 100 mV for the others (at 0.1 mA cm −2 ). Also the Na + transport number is similar for the three electrolytes ranging from 0.33 to 0.37. Full cells were prepared with layered transition metal oxide cathodes: O3-Na2/3 (Fe2/3 Mn1/3 )O2 ), P2-Na2/3 (Fe2/3 Mn1/3 )O2 and P2-Na2/3 (Mn0.8 Fe0.1 Ti0.1 )O2 . While for the O3/P2-Na2/3 (Fe2/3 Mn1/3 )O2 structures the device performance is consistent with the electrolyte properties, with the P2-Na2/3 (Mn0.8 Fe0.1 Ti0.1 )O2 cathode the N2(2O2O1)3 FSI:NaFSI electrolyte cycling extremely well. The P111i4 FSI and N2(2O2O1)3 FSI yield almost equivalent specific capacities of approximately 180 and 160 mAhg −1 respectively at C/10 rate. Graphical abstract: Highlights: Physicochemical properties of novel ionic liquid electrolytes for sodium batteries have been evaluated. The electrolytes were paired with sodium cathodes to make prototype devices. The electrolyte properties were linked to the device performance.